TINJAUAN KOMPETENSI CODER TERHADAP KEAKURATAN DAN KETEPATAN PENGKODEAN MENGGUNAKAN ICD 10 DI RUMAH SAKIT IMELDA PEKERJA INDONESIA MEDAN - Cristin Roma Dally Sipayung; Khairani Khairani (Jurnal Kesehatan Sejahtera, 2024)
Decree of the Minister of Health Number 377/MenKes/SK/III/2007 concerning the Professional Standards of Medical Recorders and Health Information states that one or the competencies that must be possessed by medical recorders is the classification and coding of diseases, health-related problems and medical actions. The purpose of this study was to determine how the influence of competence as a coder on the accuracy and precision of coding. This type of research uses qualitative research, namely research conducted with the aim of describing or analyzing the results of a state of research objectively. This research was conducted with a cross-sectional approach. In this study, the sampling technique used was Purposive sampling. With a total of 7 informants as coders at the Imelda Buruh Indonesia General Hospital. The coder staff already had a D-III education background in Recording and Health Information. The coder staff already had a D-III education background in Recording and Health Information. Medical resumes that were included in the category of incorrect diagnosis codes were 10 (31%) and the correct ones were 22 (69%). Based on the results of the study, all officers have a D-III education background in Health Recording and Information. The age of officers ranges from 21-30 years and the length of service ranges from 8 months to 6 years, and of the 7 informants, 3 respondents have good knowledge and 4 other respondents have sufficient knowledge